P69 RELATIONSHIP BETWEEN CAROTID INTIMA-MEDIA THICKNESS, ENDOTHELIAL FUNCTION, AORTIC STIFFNESS AND CARDIOVASCULAR EVENTS AMONG METABOLIC SYNDROME SUBJECTS - Ligita Ryliškytė; Rokas Navickas; Roma Puronaitė; Agnė Jucevičienė; Aleksandras Laucevičius (Artery Research, 2018)
Objective: The aim of this study was to evaluate predictive value of main arterial markers for cardiovascular (CV) events in subjects with metabolic syndrome (MetS). Methods: A prospective study enrolled 2728 middle-aged (53.9 ± 6.2 years old, 63% women) MetS patients of the Lithuanian High Cardiovascular Risk primary prevention program without overt CV disease. Subjects were followed-up for 3.9 ± 1.7 years for fatal or non-fatal myocardial infarction (MI) or stroke after their initial assessment including evaluation of carotid intima-media thickness (cIMT), aortic augmentation index (AIx), aortic pulse wave velocity (aPWV), brachial flow-mediated dilatation (FMD), carotid stiffness index, and cardio-ankle vascular index (CAVI). Results: 83 (3%) patients had at least one cardiovascular event during the follow-up period. Univariate analysis showed association of CV events with higher mean blood pressure, aPWV, AIx, cIMT, and lower FMD (all p < 0.05). Cox proportional hazard regression analysis revealed association between CV events, increase in cIMT (HR 1.31, 95% CI 1.14–1.50, p < 0.001), aPWV (HR 1.29, 95% CI 1.04–1.60, p = 0.019), AIx (HR 1.53, 95% CI 1.16–2.02, p = 0.003) and decrease in FMD (HR 0.83, 95% CI 0.71–0.97, p = 0.016) even after the adjustment for age, gender, and common CV risk factors. Using two-level survival trees analysis, we discovered relation between cIMT > 794 and higher CV risk (p < 0.001) and even higher risk with aPWV > 11.1 m/s (p = 0.023). Whereas cIMT£794 mcm together with the FMD cut-off point of 6.5% also resulted in higher risk (p = 0.003). Conclusions: Our follow-up study reveals association between CV risk, increased aortic PWV, cIMT and decreased brachial FMD among middle-aged MetS patients.